A Sensitive and Renewable Chlortoluron Molecularly Imprinted Polymer Sensor Based on the Gate‐Controlled Catalytic Electrooxidation of H2O2 on Magnetic Nano‐NiO. Issue 5 (4th March 2013) - Li, Xue; Zhang, Lianming; Wei, Xiaoping; Li, Jianping
Abstract A new sensor was fabricated by MIP synthesized on the surface of magnetic nickel(II) oxide (NiO) nanoparticles which based on the oxidation current change of H2O2. Chlortoluron was selected as template which can be detected indirectly by the decrease of the H2O2 oxidation current on the NiO nanoparticle‐modified GCE caused by the blocking access after rebinding. A high sensitivity was obtained because of the high catalytic effect of NiO nanoparticles on H2O2 oxidation. Chlortoluron was determined from 1.0×10−8/L to 1.0×10−4 mol/L, with a detection limit of 2.4×10−9 mol/L. The proposed method combines the high sensitivity of the catalytic effect and the high selectivity of the MIP technique. Water samples were assayed using the MIP sensor, and recoveries of 96.9 % to 104.7 % were obtained.